Improving nitrogen use efficiency using precision nitrogen management in wheat (Triticum aestivum L.). Issue 3 (2nd March 2021) - Varinderpal-Singh; Kunal; Gosal, S. K.; Choudhary, Rita; Singh, Reena; Adholeya, Alok
Abstract: Background : Excessive application of nitrogen (N) fertilizer in cereal crops not only decreases the N use efficiency but also accelerates greenhouse gas (GHG) emission. Aim : To improve N use efficiency in wheat ( Triticum aestivum L.) using precision N management and coating seeds with arbuscular mycorrhizal fungi (AMF). Methods : Field experiment laid out in split‐plot design was conducted to study the role of AMF consortia (four species) seed coating and different precision N management strategies in rationalizing fertilizer N use. Results : The AMF seed coating improved mycorrhization but did not improve N assimilation, grain yield, root weight, N uptake, chlorophyll value, normalized difference vegetative index, and physiological efficiency (PEN ) of applied N fertilizer. The benefits of AMF seed coating in improving N assimilation were not visible even in no‐N treatment. Precision N management using leaf color chart (LCC), chlorophyll meter (SPAD), and GreenSeeker optical sensor (GS) sustained wheat grain yield equivalent to the soil‐test based N fertilizer recommendation with the average savings of 20% N fertilizer. Precision N management strategies improved mean recovery efficiency (REN ) and partial factor productivity (PFPN ) of applied N fertilizer, respectively by 26.0% and 26.4% over the soil‐test based N management. Spectral properties measured with LCC, SPAD and GS showed good correlation ( R 2 > 0.71) with grain yield, depicting great potential of optical sensing tools in predicting grain yield and inferring need‐based fertilizer N topdressings decisions in wheat. Conclusions : Precision N management provides a potential solution to improve N nutrition in wheat while reducing nitrous oxide (N2 O) and total GHG emissions by 23.2 and 23.6%, respectively, in comparison to soil‐test based N application.